2019
DOI: 10.1164/rccm.201807-1279le
|View full text |Cite
|
Sign up to set email alerts
|

IL-5 Levels in Nasosorption and Sputosorption Correlate with Sputum Eosinophilia in Allergic Asthma

Abstract: Smoking duration alone provides stronger risk estimates of chronic obstructive pulmonary disease than pack-years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The biomarkers of type-2-high asthma are believed to develop the pathological progress of asthma. IL-4 promotes the synthesis of Ig E from B cells, and IL-13 induces goblet cell metaplasia associated with mucus hypersecretion, and IL-5 accelerates influx of eosinophils into airways (Grunig et al, 1998;Xia et al, 2018;Busse et al, 2019;Melo et al, 2019). In addition, IL-17 can drive goblet cell metaplasia and mucus hypersecretion in primary human airway epithelia (Pezzulo et al, 2019).Our results suggested that FMT treatments suppressed OVA-induced inflammatory biomarkers expression of IL-4, IL-5, IL-13, IL-17A, and Ig E, and thereby contributed to the reduction of influx of leukocytes and goblet cell metaplasia evidenced by lung histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers of type-2-high asthma are believed to develop the pathological progress of asthma. IL-4 promotes the synthesis of Ig E from B cells, and IL-13 induces goblet cell metaplasia associated with mucus hypersecretion, and IL-5 accelerates influx of eosinophils into airways (Grunig et al, 1998;Xia et al, 2018;Busse et al, 2019;Melo et al, 2019). In addition, IL-17 can drive goblet cell metaplasia and mucus hypersecretion in primary human airway epithelia (Pezzulo et al, 2019).Our results suggested that FMT treatments suppressed OVA-induced inflammatory biomarkers expression of IL-4, IL-5, IL-13, IL-17A, and Ig E, and thereby contributed to the reduction of influx of leukocytes and goblet cell metaplasia evidenced by lung histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nasal CCL‐26 is significantly correlated with sputum CCL‐26 (and IL‐13 and IL‐5) levels, which in turn is linked tightly with airway eosinophilia 17 . Minimally invasive sampling using nasosorption ® and sputosorption ® has offered some promise in providing surrogate markers of eosinophilic asthma, though these techniques require further study 43 . They are based on adsorptive materials, which allow efficient recovery of analytes (Table 1).…”
Section: Noninvasive and Minimally Invasive Diagnostics Of Allergic Amentioning
confidence: 99%
“…An example of ongoing research into non-invasive alternatives to sputum induction and more feasible measurements of airway biomarkers are through the recently developed absorptive nasal strip technology. Technology within absorptive strips permits the sampling of mucosal fluid within the upper respiratory tract109 and measurement of airway inflammatory biomarkers, successfully shown to reflect sputum eosinophilia in a recent small study in asthma 110. As a result, the powerful use of new technologies that convert ongoing advances of biomedical research into user-friendly tools that supplements and enhances current clinical tools can facilitate inter-professional communication between basic scientists, medical researchers and clinicians 111…”
Section: Strategies Related To Organizational Factorsmentioning
confidence: 99%